Pregnant individual’s lived experience of cannabis use during the COVID-19 pandemic: a qualitative study - Young-Wolff, Kelly C.; Foti, Tara R.; Green, Andrea; Iturralde, Esti; Jackson-Morris, Melanie; Does, Monique B.; Adams, Sara R.; Goler, Nancy; Conway, Amy; Ansley, Deborah; Altschuler, Andrea (Frontiers in Psychiatry, 2023)
Introduction: Quantitative studies indicate that the COVID-19 pandemic has contributed to increased rates of prenatal cannabis use. However, little is known about how the pandemic has impacted cannabis use from the perspective of pregnant individuals themselves. Our objective was to characterize COVID-19-related changes in cannabis use among pregnant individuals who used cannabis during the pandemic. Methods: We conducted 18 focus groups (from 11/17/2021-12/17/2021) with Black and White pregnant individuals aged 18+ who self-reported prenatal cannabis use during universal screening at entrance to prenatal care (at 8 weeks gestation) in Kaiser Permanente Northern California. Virtual focus groups were transcribed and analyzed using thematic analysis. Results: The sample of 53 pregnant individuals (23 Black, 30 White) was 30.3 years old (SD=5.2) on average, and most (70%) self-reported daily versus weekly or monthly prenatal cannabis use. Major themes regarding the impact of the pandemic on cannabis use included increases in use (resulting from depression, anxiety, stress, boredom), and changes in social use (less sharing of smoked cannabis products), modes of use (from smoking to other modes due to respiratory concerns) and source (from storefront retailers to delivery). Conclusions: Coping with mental health symptoms and stress were identified drivers of perceived pandemic-related increases in prenatal cannabis use in 2021. Pregnant individuals adapted their use in ways consistent with public health recommendations to decrease social contact and reduce or quit smoking to mitigate COVID-19 transmission and harms. Proactive, mental health outreach for pregnant individuals during future pandemic waves may reduce prenatal cannabis use.